Effect of in-house crowding on childhood hospital admissions for acute respiratory infection: A matched case–control study in Bangladesh. (April 2021) - Islam, Moktarul; Sultana, Zeeba Zahra; Iqbal, Adiba; Ali, Mohammad; Hossain, Ahmed
Highlights: In-house overcrowding was found to be a risk factor for hospital admission with acute respiratory infection. Overcrowding increases the risk of smoke exposure and a lack of exclusive breastfeeding. In an overcrowded house, hospitalization for acute respiratory infection can be minimized by improving sanitation and hygiene. Abstract: Objective: Despite previous studies conducted to identify potential household factors, no conclusive evidence exists regarding the effect of in-house crowding on hospitalization for acute respiratory infection (ARI) in Bangladesh. Hence, the aim of this study was to detect such an association in children aged 6–59 months. Methods: An age and sex-matched case–control study was conducted involving 348 children in Bangladesh. In-house crowding was measured by people-per-bedroom. Conditional logistic regression was performed to identify the association between in-house crowding and hospitalization for ARI. Results: In-house overcrowding was associated with a 2.9-fold (95% confidence interval 1.80–4.73) greater adjusted odds of hospitalization for ARI compared to children from less crowded houses. In-house overcrowding was common in rural areas and in households with a poor economic status. Suboptimal breastfeeding and household tobacco smoke exposure were found to prevail in overcrowded households. Conclusion: In-house overcrowding is associated with an increased risk of hospitalization for ARI in young children. Eliminating the fraction of the ARI burden due to in-house overcrowding will rely on increasing awareness regarding indoor air pollution and ventilation in the house and making efforts to avoid smoking in dwellings. Along with the management of crowding, child nutrition and exclusive breast-feeding requirements should be continued for a wide range of child health benefits.